KEVALIDAN LKPD BERBASIS PICTURE AND PICTURE MATERI SISTEM PERNAPASAN MANUSIA KELAS VIII SMP/MTs - Supiandri; Nur Kuswanti; Lina Arifah Fitriyah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Hasyim Asy'ari (Unhasy), 2021)
Abstract Science at the junior high school level can be learned as a provision of science knowledge, concepts and skills at the next level. The concept of science learning is attempted by students to understand so that maximum learning outcomes are obtained. The results of observations to students of class VIII SMP stated that teachers in studying students still used conventional methods, students liked group learning methods and discussions, students liked science learning if the teacher used pictures and writing media. The purpose of this study was to develop a cooperative student worksheet (LKPD) based on the picture and picture type on the human respiratory system material for grade VIII SMP / MTs based on validity. The use of this research instrument was in the form of a LKPD validation sheet. The assessment sheet is filled with three validators, namely expert lecturers and science teachers. The aspects assessed were didactic, construction, technical, and LKPD characteristics. The results of the validation of two material expert lecturers and junior high school science teachers showed that the picture and picture type cooperative-based LKPD was very valid to use in the human respiratory system material. The average score obtained from the two subject matter expert lecturers and junior high school science teachers is 3.63. So LKPD is suitable for use as teaching material on the human respiratory system material based on the validation results. Keywords: Picture and Picture, Human respiratory system, LKPD, Valid Abstrak: IPA pada jenjang sekolah menengah pertama dapat dibelajarkan sebagai bekal pengetahuan, konsep dan keterampilan IPA pada jenjang selanjutnya. Konsep pembelajaran IPA diusahakan peserta didik paham dan mengerti sehingga diperoleh hasil belajar maksimal. Hasil observasi kepada siswa kelas VIII SMP, menyatakan guru dalam membelajari peserta didik masih menggunakan metode konvensional, peserta didik menyukai metode pembelajaran berkelompok dan diskusi, peserta didik menyukai pembelajaran IPA jika guru menggunakan media gambar dan tulisan. Tujuan penelitian ini adalah mengembangkan lembar kerja peserta didik (LKPD) berbasis kooperatif tipe picture and picture pada materi sistem pernapasan manusia kelas VIII SMP/MTs berdasarkan validitas. Penggunaan instrument penelitian ini berupa lembar validasi LKPD. Lembar penilaian diisi tiga validator yaitu dosen ahli dan guru IPA. Aspek yang dinilai yaitu didaktik, konstruksi, teknis, dan karakteristik LKPD. Hasil validasi dari dua dosen ahli materi, dan guru IPA SMP bahwa LKPD berbasis kooperatif tipe picture and picture sangat valid digunakan pada materi sistem pernapasan manusia. Skor rata-rata yang di peroleh dari dua dosen ahli materi, dan guru IPA SMP yaitu 3,63. Jadi LKPD layak di gunakan sebagai bahan ajar pada materi sistem pernapasan manusia berdasarkan hasil validasi. Kata kunci: Picture and picture, Sistem pernapasan manusia, LKPD, Valid